Race And Gender Discrimination Reflected In The Tate Taylor's The Help Movie (2011): A Feminist Approach - Hartatik, Hartatik; , Dr. Phil. Dewi Candraningrum, M. Ed; , Nur Hidayat, S.Pd (2013)
This study about how race and gender discrimination reflected in The Help movie by using feminist approach. The objective of the study to analyze the movie based on its structural elements and analyze the movie based on feminist approach. The writer uses qualitative method for analyzing the movie. The object of the study is Tate Taylor‟s The Help movie was released on 2011 in the United Stated. The primary data is taken from the movie itself and the secondary data sources are other informations that are relevant to the subject matter. The method of the data collection are watching the movie repeatedly, taking notes of important parts, arranging the data into several groups based on its theoretical category, selecting particular parts considered important and relevant for analysis, drawing conclusion and formulate its pedagogical suggestion. The techniques of data analysis are as follows: first analyze the data based on its structural element and second step analyze the data based on the feminist approach. The conclusions of the study are based on structural analysis of the movie and based on Feminist analysis. The structural elements of the movie are related into unity. Second based on Feminist analysis, in this movie there are discrimination of race and gender between white people and black people. The effects of the discrimination are the black people who are poorer and have lower class than white people.